Solar wind power likely governs Uranus’ thermosphere temperature - Masters,A (Geophysical Research Letters, 2024)
Observations of Uranus in the near-infrared by ground-based telescopes from 1992 to 2018 have shown that the planet's upper atmosphere (thermosphere) steadily cooled from ∼700 to ∼450 K. We explain this cooling as due to the concurrent decline in the power of the solar wind incident on Uranus' magnetic field, which has dropped by ∼50% over the same period due to solar activity trends longer than the 11-year solar cycle. Uranus' thermosphere appears to be more strongly governed by the solar wind than any other planet where we have assessed this coupling so far. Uranus' total auroral power may also have declined, in contrast with the power of the radio aurora that we expect has been predominantly modulated by the solar cycle. In the absence of strong local driving, planets with sufficiently large magnetospheres may also have thermospheres predominantly governed by the stellar wind, rather than stellar radiation.